Implementation of Songket Weaving Dance Extracurricular Activities at State Senior High School 4 Palembang - Muzayana, Laili Yulia; Hasan, Hasan (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The title of this study is the implementation of songket weaving dance extracurricular activities at SMA Negeri 4 Palembang. The formulation of the problem in this study is how is the implementation of extracurricular activities of songket weaving dance at SMA Negeri 4 Palembang. From these problems, the purpose of this study is to find out how the extracurricular activities of the songket weaving dance are carried out at SMA Negeri 4 Palembang. The research method used in this research is descriptive qualitative method. The object of this research is the extracurricular learning of songket weaving at SMA Negeri 4 Palembang. The data collection techniques used in this study were observation techniques, interview techniques and documentation techniques. Songket weaving extracurricular learning from the results of research data that has been carried out by the author either through observation techniques, interview techniques and documentation shows that it looks very good because the strategy used by the coach in his learning produces maximum results or is already said to be very good. Where in the dance extracurricular learning process it has a positive effect on coaches and students as evidenced by seeing the learning process of students who are very enthusiastic and strengthened from the results of the evaluation given it is found that students get an average score of 86, with the highest score being 88 and the lowest being 80. Thus the insight and intellect of students can develop and contribute to increasing the extracurricular art of songket weaving at SMA N 4 Palembang.